Laparoscopic herniotomy with orchidopexy: our experience and a review of literature - Shandilaya, Umang; Joshi, Abhijit S. (International Surgery Journal, 2025)
Background: Congenital hernia and undescended testis are significant pediatric surgical conditions traditionally managed through open techniques. With advances in minimally invasive surgery, laparoscopic approaches now offer an alternative for treating these conditions. Methods: We present a retrospective study outlining our experience with laparoscopic herniotomy and, when indicated, laparoscopic orchidopexy in paediatric patients. In all cases, pneumoperitoneum pressures were adjusted appropriately to ensure procedural safety and efficacy. Results: Our findings demonstrate that laparoscopic repair of both congenital hernia and undescended testis is technically feasible and effective in children. All procedures were completed successfully, with minimal complications and satisfactory postoperative outcomes. Conclusion: Laparoscopic management of congenital hernias and undescended testes is a safe and effective alternative to open surgery in paediatric patients, given the availability of an advanced surgical setup and experienced personnel.